PISA-Like Questions on News Items: A Novel Approach to Reading Literacy - Nisphi, Medio; Alwi, Zahra; Oktarina, Santi (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2023)
Due to PISA inconsistencies and three years of learning loss, Indonesia's new curriculum paradigm focuses on core skills, particularly reading literacy. In 2021, the minimum competency assessment (MCA) took the place of the national assessment, and since then it has had teachers and students worried about academic success. This research aims to develop valid, practical, and effective PISA-like reading questions to prepare students for the MCA. The development study was used as a grand framework of design research, consisting of a preliminary evaluation stage and a formative evaluation stage. This research involved 45 15-year-old middle school students of varied reading literacy levels. The analysis in this research was conducted qualitatively based on data from interviews, document reviews, observations, and tests to see how students worked on PISA-like reading literacy questions. This research produced valid and practical PISA-like reading literacy questions according to the PISA 2022 framework. In terms of content, the PISA-like reading literacy questions focus on topics of news items. In terms of context, students explore new situations, especially in relation to health. Student competences are measured at the application and reasoning levels. This study suggests that PISA-like reading literacy questions can be a source of inspiration for teachers in designing questions, and they can be used to improve students' literacy skills.